2000
DOI: 10.1096/fasebj.14.1.208
|View full text |Cite
|
Sign up to set email alerts
|

Hemeoxygenase expression in human placenta and placental bed implies a role in regulation of trophoblast invasion and placental function

Abstract: The purpose of this study was to examine the expression of hemeoxygenases HO-1 and HO-2, which are responsible for the production of carbon monoxide (CO), in the human placenta and placental bed and to determine the role of inhibitors of HO on placental perfusion pressure. We hypothesized that HO is expressed within the placenta and that invading cytotrophoblast cells (CTB) express HO isoforms. The expression of HO-1 and HO-2 was studied on placenta and placental bed biopsies, obtained using a transcervical sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
106
2
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 140 publications
(120 citation statements)
references
References 63 publications
(60 reference statements)
10
106
2
2
Order By: Relevance
“…The growth enhancing action of HO-1 may arise from its ability to enhance fetal oxygenation and substrate delivery. Induction of placental HO-1 expression augments placental blood flow, while inhibition of HO-1 activity increases resistance in the perfused placenta (Ahmed et al, 2000b;Lyall et al, 2000;McLaughlin et al, 2000). This vasodepressor function of HO-1 is likely mediated via the liberation of CO since CO relaxes blood vessels in numerous vascular beds, including human placenta (Durante and Schafer, 1998;Wang, 1998;Zhang et al, 2001;Bainbridge et al, 2002).…”
Section: Ho-1 and Growth Regulationmentioning
confidence: 99%
“…The growth enhancing action of HO-1 may arise from its ability to enhance fetal oxygenation and substrate delivery. Induction of placental HO-1 expression augments placental blood flow, while inhibition of HO-1 activity increases resistance in the perfused placenta (Ahmed et al, 2000b;Lyall et al, 2000;McLaughlin et al, 2000). This vasodepressor function of HO-1 is likely mediated via the liberation of CO since CO relaxes blood vessels in numerous vascular beds, including human placenta (Durante and Schafer, 1998;Wang, 1998;Zhang et al, 2001;Bainbridge et al, 2002).…”
Section: Ho-1 and Growth Regulationmentioning
confidence: 99%
“…Ozawa et al (2002) suggested that CdCl 2 -induced HO-1 expression in Leydig cells appears to regulate apoptosis of premeiotic germ cells and thereby modulates spermatogenesis under conditions of stress; in addition, a protective function of spermatogenic cells under conditions of thermal stress was suggested for HO-1 induction (Maines & Ewing 1996). Both HO isoforms are also expressed in human placenta and a functional role in trophoblast invasion and in spiral artery transformation together with the function of CO as a vasodilator in the fetoplacental circulation has also been suggested (Lyall et al 2000, Barber et al 2001, Navarra et al 2001. It has also been demonstrated that Cd 2+ stimulates HO activity in the ovary (Maines & Kutty 1983).…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24] Heme oxygenase, the key enzyme involved in CO generation, is widely distributed throughout tissues and organs, including the placenta. 25,26 There is increasing evidence that CO is required for normal placental development and function; endogenous CO production may regulate trophoblast migration and organization 1,25,26 and play a hemodynamic role. 27 Further, women who have PE have significantly decreased CO concentrations in their exhaled breath compared with healthy pregnant women, 28,29 suggesting an endogenous regulatory role of this gaseous compound in the maintenance of healthy pregnancies.…”
mentioning
confidence: 99%